Deficiency of interleukin-1 receptor antagonist: A systematic review - Wérgila Ruana Gonçalves Barros,; Jucier Gonçalves Júnior, (Archives of Rheumatology, 2024)
Objectives: The study aimed to conduct a systematic literature review of the epidemiology, pathophysiology, clinical presentation, diagnosis, and treatment of patients with deficiency of the interleukin-1 receptor antagonist (DIRA) and determine the practical contributions that the current scientific literature offers concerning the clinical and epidemiological aspects of DIRA. Materials and methods: A systematic review of the literature was conducted in the PubMed, Scopus, Web of Science, and the Virtual Health Library databases between January 2009 and June 2024 in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. The following MeSH descriptors were used: “interleukin-1 receptor antagonist deficiency,” “epidemiology,” “clinical manifestations,” “treatment,” and “physiopathology.” Results: Of the 3,749 articles, 18 met the eligibility criteria. The findings were divided by heuristic questions into three groups: “epidemiological and genetic aspects of patients with DIRA,” “clinical and laboratory characterization in DIRA,” and “therapeutic approach to patients with DIRA.” Conclusion: DIRA appears to be more common in males around four years of age. Several IL-1RN mutations were described, varying according to the geographic location. The most common symptoms were fever, followed by osteoarticular manifestations (arthralgia, muscle contracture, fracture, osteolytic lesions, and osteomyelitis), nail changes, pneumonia, venous thrombosis, and, in severe cases, multiple organ failure. There were no specific laboratory markers. Canakinumab was the drug of choice; however, glucocorticoids, rilonacept, and anakinra have been used.